How can servant leadership arouse to innovative work behavior? - Shofia Amin; Zulfina Adriani; Fitri Widiastuti (Faculty of Economics and Business Mulawarman University, 2022)
This study examined the role of servant leadership in encouraging innovative work behavior of civil servants through increased employee engagement. This study used a quantitative method by distributing a list of questions to 116 Aparatur Sipil Negara (ASN) from several institutions in Jambi City. The primary data were analyzed using SEM-SmartPLS. The results showed that servant leadership had no significant positive effect on innovative work behavior, but servant leadership positively affected employee engagement. Moreover, employee engagement also has a significant positive impact on innovative work behavior. Thus, employee engagement is a complete mediation in the relationship between servant leadership and innovative work behavior. The results indicated that innovative behavior could be increased by enhancing employee engagement stimulated by servant leadership.